An analysis of the effects of mergers and acquisitions on the financial performance and strategy of Deutsche Boerse Group AG - Kazakova, Irina (2024)
This thesis examines the impact of mergers and acquisitions on Deutsche Börse Group's financial performance and strategy from 2000 to 2022. It analyzes key financial metrics like ROA, ROE, EPS, and Net Profit Margin to evaluate the outcomes of Deutsche Börse Group’s M&A activities. The analysis finds that M&As significantly influence DBG’s growth and diversification, although their impact on financial performance is complex and varies due to multiple factors. It highlights DBG's strategic adaptability and regulatory compliance in response to different challenges, particularly notable in attempts to merge with NYSE Euronext and LSE. The research contributes to understanding the efficacy of M&A in the financial sector, emphasizing the importance of strategic alignment and adaptability in M&A decisions.